2011
DOI: 10.1080/15350770.2011.568340
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Intergenerational Gap in Therapeutic Activity Delivery Between Younger Professional Caregivers and Older Adults Living With Dementia

Abstract: Many older individuals have cohort-specific knowledge that may not be known by young caregivers. By providing familiar information, using Montessori principles that key into the remaining abilities of those with dementia, it is possible for the younger caregivers to successfully facilitate satisfying, interactive programs. Forty activity directors and staff, age 25-50, in long-term care settings interacted with residents age 56-100 in groups of 10 or more in both an activity intervention and standard activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…3 studies were performed on 4 subjects, 40,46 9 studies were conducted on 5-18 subjects (average of n = 11.22) 28, 33,34,43,45,48,49,53,57 and 6 studies were done on 20-30 people (average of n = 24). 4,30,35,37,42,55 The number of participants in 2 studies was between 30 and 35 (average of n = 33.5), 39 the number of samples in another 2 studies was 40 36,54 and the sample size in the other 2 studies was 43. 38,50 Also, 4 studies involved 44 to 64 participants (average of n = 53.5).…”
Section: Sample Population Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 studies were performed on 4 subjects, 40,46 9 studies were conducted on 5-18 subjects (average of n = 11.22) 28, 33,34,43,45,48,49,53,57 and 6 studies were done on 20-30 people (average of n = 24). 4,30,35,37,42,55 The number of participants in 2 studies was between 30 and 35 (average of n = 33.5), 39 the number of samples in another 2 studies was 40 36,54 and the sample size in the other 2 studies was 43. 38,50 Also, 4 studies involved 44 to 64 participants (average of n = 53.5).…”
Section: Sample Population Characteristicsmentioning
confidence: 99%
“…4,21,29,34,35,39,47 3 studies included samples with moderate to severe dementia 37,48,57 and 2 studies included patients with moderate dementia. 33,54 Also, 4 studies were performed on patients with mild to severe dementia. 28,32,51,52 In one study, it was mentioned that the length of time subjects had been diagnosed with dementia was 25 months 55 and, in another study, it had been reported between 25 and 37 months.…”
Section: Sample Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exceptions include findings on reducing agitation either within session of Montessori‐based activity or with complementary effect of acupressure . Besides, the type of training provided for facilitators of Montessori‐based activities was inconsistently reported in literatures, though Montessori‐based activities have been delivered by different kinds of facilitators including allied health professionals and nonprofessionals . Therefore, it is uncertain on whether the quality of Montessori‐based activities implemented is consistent across studies and Montessori‐based activities is effective in reducing agitation persistent in daily life of long‐term care home residents with dementia …”
Section: Introductionmentioning
confidence: 99%